BlastGUI: A Python‐based Cross‐platform Local BLAST Visualization Software. Issue 4 (5th November 2019) - Du, Zongjun; Wu, Qing; Wang, Tianzhu; Chen, Defang; Huang, Xiaoli; Yang, Wei; Luo, Wei
Abstract: Many researchers use BLAST+ software to build databases and perform sequence alignments. However, command‐line operations are required and this created a barrier for researchers with weak computer skills. Therefore, we designed BlastGUI, a Local BLAST visualization software based on Python programming language, to enable users to build databases and perform sequence filtering and sequence alignment through a graphical user interface. The operation visualization, automatic sequence filtering, and cross‐platform utilization significantly facilitate biological data analysis and information mining. Our designed software is freely available under the terms of the GNU GPLv3 at https://github.com/byemaxx/BlastGUI. Abstract :